CFD Benchmark Tests for Indoor Environmental Problems: Part 3 Numerical Thermal Manikins - Kazuhide Ito; Kiao Inthavong; Takashi Kurabuchi; Toshikatsu Ueda; Tomoyuki Endo; Toshiaki Omori; Hiroki Ono; Shinsuke Kato; Koji Sakai; Yoshihide Suwa; Hiroshi Matsumoto; Hajime Yoshino; et al. (International Journal of Architectural Engineering Technology, 2015)
Recent indoor environmental design is requested to create comfortable and safety space in addition to the maximizing the energy conservation performance in buildings. In this point of view, it is important to enhance the prediction accuracy of indoor environmental quality in design stage. Commercial Computational Fluid Dynamics (CFD) software is practically applied in indoor environmental design recent years but the prediction accuracy of CFD simulation depends on the understanding for the fundamentals of fluid dynamics and the setting of appropriate boundary and numerical conditions as well. The series of this study aimed to provide with the practical information such as prediction accuracy and problematic areas related to CFD applications in indoor environment, air conditioning and ventilation, and then performed benchmark tests and reported the results. Especially in this Part 3, benchmark test results for numerical thermal manikins were introduced. SST k-ω model with fine mesh could provide sufficient accurate results and showed good agreement with experimental results.